How to strengthen societal impact of research and innovation? Lessons learned from an explanatory research-on-research study on participatory knowledge infrastructures funded by the Netherlands Organization for Health Research and Development - Wija Oortwijn; Wendy Reijmerink; Jet Bussemaker (BMC, 2024)
Abstract Background Scientific research and innovation can generate societal impact via different pathways. Productive interactions, such as collaboration between researchers and relevant stakeholders, play an important role and have increasingly gained interest of health funders around the globe. What works, how and why in research partnerships to generate societal impact in terms of knowledge utilisation is still not well-known. To explore these issues, the Netherlands Organization for Health Research and Development (ZonMw) initiated an exploratory research-on-research study with a focus on participatory knowledge infrastructures (PKIs) that they fund in the field of public health and healthcare. PKIs are sustainable infrastructures in which knowledge production, dissemination and utilisation takes place via committed collaboration between researchers and stakeholders from policy, practice and/or education. Examples are learning networks, academic collaborative centres, care networks and living labs. The aim of the study was twofold: to gain insights in what constitutes effective collaboration in PKIs; and to learn and improve the research governance, particularly of ZonMw as part of their dissemination and implementation activities. Methods During 2020-2022, we conducted a literature review on long-term research partnerships, analysed available documentation of twenty ZonMw-funded PKIs, surveyed participants of the 2021 European Implementation Event, interviewed steering committee members, organized a Group Decision Room with lecturers, and validated the findings with key experts. Results We identified eight mechanisms ('how and why') that are conditional for effective collaboration in PKIs: transdisciplinary collaboration; defining a shared ambition; doing justice to everyone's interests; investing in personal relationships; a professional organisation or structure; a meaningful collaborative process; mutual trust, sufficient time for and continuity of collaboration. Several factors ('what') may hinder (e.g., lack of ownership or structural funding) or facilitate (e.g., stakeholder commitment, embeddedness in an organisation or policy) effective collaboration in research partnerships. Conclusion To use the study results in policy, practice, education, and/or (further) research, cultural and behavioural change of all stakeholders is needed. To facilitate this, we provide recommendations for funding organisations, particularly ZonMw and its partners within the relevant knowledge ecosystem. It is meant as a roadmap towards the realisation and demonstration of societal impact of (health) research and innovation in the upcoming years.